Estructuración de un modelo de gestión basado en el "Lean Management" aplicable al area de comercialización de la compañía de transporte San Francisco de Chillogallo S.A. - Maldonado Noroña, Ximena del Rosario (2012)
By engaging the Company to serve urban passenger transport in the Metropolitan District of Quito, there arises a need for automotive belonging to its fleet and it is desired to establish and maintain maintenance workshops and services for vehicles; install services lubricants, washing vehicles, mechanical and finally all activities related to transportation; for such virtue and decision AGM it was decided to create the "AUTO SERVICE SAN FRANCISCO" which starts its business since November 12, 2007.